Macroplastic Debris Transfer in Rivers: A Travel Distance Approach - Newbould, Robert A.; Powell, D. Mark; Whelan, Michael J. (Frontiers in Water, 2021)
Plastic accumulation in the marine environment is a major concern given the harmful effects and longevity of plastics at sea. Although rivers are likely to significantly contribute to the flux of plastic to marine systems, the behaviour of plastic debris in fluvial systems remains poorly understood and estimates of riverine plastic flux derived from field measurements and modelling efforts are highly uncertain. This paper presents a new probabilistic model of plastic transport in rivers which describes the main processes controlling plastic displacement and which predicts the statistical distribution of travel distances for individual items of buoyant macroplastic debris. Macroplastic transport is controlled by retention in temporary stores (or traps) created by vegetation, bank roughness elements and other obstacles. The behaviour of these traps is represented in the model via a series of Bernoulli trials conducted in a Monte Carlo simulation framework. The model was applied to a tracer experiment in a small 1.1 km river reach. Three replicates were used for calibration and three for validation. For each replicate, 90 closed air-filled polyethylene terephthalate (PET) bottles were introduced at the upstream end of the reach and the location of each bottle was recorded after 24 h. Bottles were chosen as “model” macroplastic litter items given their high usage and littering rate. Travel distances were low. The average and maximum distances travelled over 24 h were 231 m and 1.1 km, respectively. They were also variable. The coefficient of variation of travel distances was 0.94. Spatial patterns were controlled by the location and characteristics of discrete traps. The model was able to describe the observed travel distance distributions reasonably well, suggesting that modelling plastic behaviour in longer reaches and even whole catchments using a stochastic travel distance approach is feasible. The approach has the potential to improve estimates of river plastic flux, although significant knowledge gaps remain (e.g., the rate and location of plastic supply to river systems, the transport behaviours of different types of plastic debris and trap effectiveness in different types of river system, season, and discharge).